Experimental investigation of PWM laser standoff distance control for power diode based LBM. (February 2023) - Vasanth, S.; Muthuramalingam, T.; Surya Prakash, S.; Shriman Raghav, S.; Logeshwaran, G.
Highlights: PWM control can enhance the diode based LBM process on leather cutting. Circular shape cutting can be done effectively on diode based laser beam machining. ESP32 microcontroller can reduce the carbonization. ESP32 can produce lower kerf width. Adaptive change of PWM can enhance the diode based LBM process. Abstract: Laser Beam Cutting (LBC) is a non-traditional excellent material processing technique preferred for robust, versatile and durable materials like leather, as it offers various benefits such as excellent accuracy and minimal tool wear due to the lack of contact between the specimen and the nozzle. In this investigation, power diode laser was preferred for leather cutting because of its longevity, monochromaticity and tunability. Pulse Width Modulation (PWM) is an input parameter that is tuned to control the output optical power of the diode laser in this study. There is no viable method available in the field of direct adaptive control for PWM in the application of diode laser leather cutting. Hence an attempt has been proposed in this present study to control and investigate the machinability of leather by implementing the diode based LBC technology and standoff distance (SOD) control using VL6180X time of flight sensor, with indirect adaptive PWM control approach. The cutting trials were conducted on chrome tanned goat leather of thickness 0.8 mm and also this investigation reports the carbonization values and kerf width during leather cutting. It was identified that the closed loop PWM control could reduce the carbonization from 34.645 % to 30.424 % with SOD control of 20 mm. It was observed that PWM based control can enhance the machining process in an effective way.